Aqueous and hydroalcoholic extracts of Black Maca (Lepidium meyenii) improve scopolamine-induced memory impairment in mice - Rubio J. (2007)
Peng Bo, Hu Qin, Xiaming Wen, Yang Keli, Jiang Zhen and Sandra Yucra are acknowledged for their help in this study. Special thanks to the joint financial support for this work from the National Nature Science Foundation of China, NSFC in 2004 (30472016/C03020701) and from Peruvian National Council of Sciences, Technology and Innovation (CONCYTEC) through the grant PROCOM 2005 and support for travel. Julio Rubio was on leave from the Universidad Peruana Cayetano Heredia, Peru (UPCH) through the Memorandum of Understanding between IMPLAD, CONCYTEC and UPCH.